A narrative inquiry of socio-scientific issues-based e-learning development in biology to promote student health literacy - Agung Wijaya Subiantoro; Rio C. Handziko; Yuni Wibowo (Universitas Negeri Jakarta, 2021)
Study on e-learning implementation has been growing as a great interest particularly in biology education research and practice. Whilst a number of research has shown various modes of e-learning, however, there is still a lack of understanding on how e-learning can be applied for health literacy orientation in biology instruction. This research aimed to develop a conceptual framework of SSI-based e-learning in biology to promote student health literacy. This research was conducted in narrative inquiry design. Nine people including five biology teachers, two experts in health education and two science teachers who are practitioners in e-learning implementation were voluntarily participated in this research. Data of this research are experiences, knowledge, or perspectives that were expressed by participants and were collected through semi-structured interviews. Thematic analysis approach was employed to analyse the data in three stages with trustworthiness and authenticity were applied for quality standard. Research findings show that there are three main aspects that need to be considered in developing an intended framework. These are: 1) e-learning platform could be used, 2) SSI-based learning pathways arranged in e-learning mode, and 3) additional e-learning elements need to be provided. Hence, these three aspects play essential roles in underpinning the framework of SSI-based e-learning in biology to promote student health literacy.